A Study of the Soya-Based Lactose-Free formulae Market from Customers (Paediatricians) Perspective in India - Shetti, Geeta; Kulkarni, D. G. (SFIMAR Research Review, 2016)
Child mortality rate has been a major concern across the globe and reasons are frequently studied. Several local and global agencies including the World Health Organisation(WHO) come up with concerns and possible solutions to arrest this rate. Among the major reasons for child mortality, diarrhoea is the second greatest killer, and also a leading cause of malnutrition across the world that grips the attention of this report. Special awareness is required to combat consequences. It has been observed that Soya-based lactose free formulae can help improve diarrheal parameters. This study explores the dimensions of such supplementary food formulas in the context of Indian market.